Twin Anemia-Polycythemia Sequence: What do we know about it? - Galvão,Joana (2021)
Abstract Twin anemia-polycythemia sequence (TAPS) is a pathology of monochorionic twin pregnancy that results from slow unequal blood distribution that causes the discrepancy of hemoglobin values between the anemic fetus (the donor) and the polycythemic one (the recipient). Unlike twin-to-twin transfusion syndrome (TTTS), twin oligohydramnios-polyhydramnios sequence (TOPS) is not present in TAPS. TAPS might occur spontaneously or after laser treatment for TTTS. Prenatal diagnosis relies on twin discrepant values of middle-cerebral-artery (MCA) peak-systolic-velocity (PSV). Management options include laser surgery, expectant management, intrauterine transfusions, and delivery. This review aims to summarize the research made on the last 7 years on TAPS.